Quality of Work Life and Commitment in Oil and Gas Industry: A Post-Transition Aftermath - Ristyan, Windar; Indarti, Sri; Machasin; H. Halim, Edyanus; Suci, Afred (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The present research aims to investigate the explanatory effects of demographic factors, such as gender, generation types, and tenure, on employees’ post-transition QWL and commitment in the oil and gas sectors. This research used two oil and gas companies in Indonesia, one state-owned and one private company, that have just transitioned from foreign to national management. A survey of 159 employees was conducted to collect primary data. The analysis employed descriptive statistics, independent t-test, ANOVA, and regression analysis. While gender did not elicit significant differences, generation types and tenure, on the other hand, generated substantial differences in employees' QWL and commitment. The X-er employees and those who had higher tenure in the post-transition scenario demonstrated the highest QWL and commitment. Furthermore, the most pronounced effect of QWL on commitment was found among employees with lower tenures than those with moderate or higher tenures. This study offers a novel approach by applying psychological contract theory to explain how QWL influences employee commitment within the oil and gas sector following a transition from foreign to national ownership and management. In addition, the use of gender, generation type, and tenure as explanatory variables offers fresh insights into understanding the dynamics of employee commitment in the transitional context.